Effect of Substrate Temperature on Droplet Evaporation Mode and Temperature Field Distribution - Huang Xinlei; Liu Bin; Li Qinqin; Yang Wenzhe; Chen Aiqiang (Zhileng xuebao)
The droplet evaporation process of Al2O3 nanofluid droplets with particle size 50 nm and mass fraction 0.1% were investigated experimentally. The actual evaporation behaviors of four types of heating temperatures (30, 47, 64, and 81 ℃) on the glass-slide substrate were studied to investigate the temperature field distribution of the gas liquid interface. The variation in the contact angle and contact line radius, and the temperature distribution of nanofluid droplets during evaporation were obtained, and the evaporation junctions were photographed with a microscope. As a result, the sedimentary patterns left by the evaporation of the bottom plate were observed. The results show that the difference in evaporation temperature does not have a significant effect on the evaporation mode. However, as the heating temperature of the bottom plate increases, the evaporation time is considerably shortened (the longest evaporation time is 10 times of the shortest). The initial Marangoni number increases gradually with the bottom plate temperature, but the Marangoni flow is inhibited with continuous evaporation.